The impact of environmental regulations on the location of pollution-intensive industries in China. (1st April 2017) - Shen, Jing; Wei, Yehua Dennis; Yang, Zi
Abstract: This study analyzes location and relocation patterns of pollution-intensive industries (PIIs) in Guangdong province, China from 2000 to 2013 to evaluate the role of environmental regulation and test the Pollution Haven Hypothesis. Panel data regressions are used to evaluate links between environmental regulation and location of PIIs, with an explicit focus on administrative structures and policies. We find that hundreds of PIIs relocated their business operations from the more developed Pearl River Delta (PRD) to the peripheral Non-Pearl River Delta (NPRD). Modeling results suggest a politically and categorically variable role of environmental regulation on location decisions involving PIIs. China's energy saving and airborne emissions reduction policies, including sulfur dioxide emission reduction targets, pushed heavy air-polluting industries from the PRD to the NPRD. However, policies requiring construction of sewage treatment plants in relocation parks prevented the formation of a pollution haven refuge for industrial wastewater in the NPRD, suggesting that the selected environmental regulations can inhibit the formation of new pollution havens. Highlights: We analyze the location and migration patterns of pollution-intensive industries. Pollution-intensive enterprises relocate operations from developed to less developed areas. Relocations are related to targeted environmental regulation (ER). This paper confirms the existence of the pollution haven hypothesis in Guangdong. Suitable ER policies control and prevent pollution havens' growth and expansion.